Madrasah Head's Strategy for Improving Self-Efficacy and Teacher Performance in Islamic Senior High School - Harahap, Khoirul Saleh; Hadijaya, Yusuf; Nasution, Inom (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
The head of the madrasah plays an important role in managing and developing human resources in the educational environment. This qualitative research with a phenomenological approach aims to gain an in-depth understanding of the experiences and perceptions of teachers and madrasah heads related to self-efficacy and performance in MAN 2 Model Medan. Data collection was obtained through semi-structured interviews, observations, and documentation. The data sources were obtained from teachers and madrasah heads and then analyzed using the Miles-Huberman technique. The study results show that: 1) internal and external factors influence the efficacy and performance of teachers in MAN 2 Model Medan. Internal factors are age, teaching experience, and ability to master technology. In contrast, external factors are salary, peer support, and emotional condition, and 2) Strategies used by madrasah heads to improve the efficacy and performance of teachers in MAN 2 Model Medan are implementing strategic management, providing motivation, instruction, good supervision, and creating a conducive learning environment. Through the right strategy, it appears that the head of the madrasah has succeeded in improving the effectiveness and performance of teachers in MAN 2 Model Medan.